UNDERSTANDING PERCEPTION AND MOTIVATION IN SHARING INFORMATION BY DIGITAL NATIVES IN SOCIAL MEDIA - Nurpratama, Muhammad Rifky (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: The phenomenon of sharing information by all members of the public, especially digital natives. The phenomenon of sharing information is most visible done on social media such as WhatsApp, Instagram and line. Information sharing activities seem easy to do, especially on social media with a variety of features that have been provided and a variety of information that is spread. Even sharing information can have an impact, both positive like increasing knowledge or negative impacts such as creating information hoaxes.Purpose: Not yet known explicitly actually what lies behind someone, especially the digital generation natives share information on social media. To find out what is the background of someone sharing information on social media, therefore this study wants to find out from the aspect of perception and motivation regarding information sharing activities carried out by digital natives on social media.Method: This research uses quantitative methods, while the test carried out is path analysis. The population and sample of this study were S2 students in Information Management and Library and S1 Faculty of Social and Politics UGM. The population was chosen because they want to know the differences in perceptions and motivations of digital generations from the perspective of the level of education and age, apart from the social aspects of each student in sharing information on social media.Findings: The results of this study found that the perception of MIP students' information sharing was higher than that of FISIPOL students, but on the contrary, the motivation to share information on FISIPOL students was higher than MIP students. The difference is based on the age difference of MIP students who are more mature than FISIPOL students so that their perceptions about sharing information are wiser, but the motivation of FISIPOL students is higher because sharing information is not only for formal matters but also for informal matters such as finding one's reputation and pursuing prizes.Conclusion: Digital natives' perception in sharing information on social media is sharing information because it is seen to be beneficial to other individuals, sharing information is fun and can invite others to jointly understand and discuss together the latest information. For digital natives motivation in sharing information on social media, intrinsically to meet self-satisfaction. Examples such as being able to add insight and can discuss with other individuals. Whereas extrinsically is the motivation to share information because it can help others, especially when the information they have is useful and worth sharing. In terms of information sharing activities themselves, the digital natives really understand and pay attention to the type of information and the quality of information that will be shared before they share it with a wide audience.